Determinant of Whistleblowing Intention with Remuneration as Moderation in Indonesian Open University - Junita Dinna Winnanda; Harnovinsah; Nurmala Ahmar (JFBA: Journal of Financial and Behavioural Accounting, 2023)
The purpose of this research is to investigate the factors that influence whistleblowing intentions at the Indonesian Open University, with remuneration as a moderating variable. The research sample included 138 finance managers and state property managers from the Indonesian Open University. Because it supports income addition for Indonesian Open University employees, remuneration is used as a moderating variable. The research method employed is quantitative with primary data approach, namely a closed questionnaire assessed via Google Forms. This research found that the three independent variables namely attitude, organizational commitment, and personal costs have a significant influence on whistleblowing intentions. Remuneration as a moderating variable found to moderate the effect of organizational commitment on whistleblowing intentions. The contribution of this research is a discussion of research findings and differences with previous findings and related theories, and the findings can be implemented in the Indonesian Open University's whistleblowing system.